2018
DOI: 10.1002/cbic.201800740
|View full text |Cite
|
Sign up to set email alerts
|

Triple Orthogonal Labeling of Glycans by Applying Photoclick Chemistry

Abstract: Bioorthogonal labeling of multiple biomolecules is of current interest in chemical biology. Metabolic glycoengineering (MGE) has been shown to be an appropriate approach to visualizing carbohydrates. Here, we report that the nitrile imine–alkene cycloaddition (photoclick reaction) is a suitable ligation reaction in MGE. Using a mannosamine derivative with an acrylamide reporter group that is efficiently metabolized by cells and that quickly reacts in the photoclick reaction, we labeled sialic acids on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 56 publications
0
34
0
2
Order By: Relevance
“…Cells with norbornene‐bearing surfaces have now been successfully generated, which could allow for light‐enabled precise spatial control of cell–cell interactions . However, although norbornene‐sugar incorporation efficiency is still limited in present attempts, other photocrosslinkable groups have shown promising results (i.e., acrylamide) . Cells exhibiting triple‐orthogonal surface engineering have also been reported, which could allow for more complex heterogenous configurations of cell–cell interactions .…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells with norbornene‐bearing surfaces have now been successfully generated, which could allow for light‐enabled precise spatial control of cell–cell interactions . However, although norbornene‐sugar incorporation efficiency is still limited in present attempts, other photocrosslinkable groups have shown promising results (i.e., acrylamide) . Cells exhibiting triple‐orthogonal surface engineering have also been reported, which could allow for more complex heterogenous configurations of cell–cell interactions .…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
“…However, although norbornene‐sugar incorporation efficiency is still limited in present attempts, other photocrosslinkable groups have shown promising results (i.e., acrylamide) . Cells exhibiting triple‐orthogonal surface engineering have also been reported, which could allow for more complex heterogenous configurations of cell–cell interactions . Alternatively, cell surface‐grafting strategies are starting to emerge, either as controlled radical polymerization or anchoring telechelic synthetic polymers, in order to re‐engineer cell surface functionality and interactions …”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
“…HEK293T cells treated with all three molecules at once showed independent labeling of each, demonstrating that all three reactions can occur simultaneously with limited background. 102 Some salvage pathways are so tolerant of structural changes that the same sugar can be functionalized with two different bioorthogonal handles. Feng et al demonstrated this possibility with 9AzSiaNAlk and 9AzSiaNAz.…”
Section: Multi-labelingmentioning
confidence: 99%
“…Moving beyond the metabolic labelling of single types of monosaccharides, several groups have explored combinations of multiple bioorthogonal ligations for the simultaneous labelling of two glycan populations on the same cells [ 48 , 56 , 58 ]. Building on the latest advances in bioorthogonal chemistry, a triple labelling of cell surface glycans using ManNAc derivatives with three different tags has also been described [ 59 ]. The Vocadlo group used a dual bioorthogonal strategy to verify the existence of co-translational O-GlcNAcylation, a modification that had thus far been believed to occur only post-translationally [ 60 ].…”
Section: Metabolic Oligosaccharide Engineeringmentioning
confidence: 99%